A computational framework for investigating bacteria transport in microvasculature. Issue 4 (12th March 2023) - Windes, Peter; Tafti, Danesh K.; Behkam, Bahareh
Abstract: Blood-borne bacteria disseminate in tissue through microvasculature or capillaries. Capillary size, presence of red blood cells (RBCs), and bacteria motility affect bacteria intracapillary transport, an important yet largely unexplored phenomenon. Computational description of the system comprising interactions between plasma, RBCs, and motile bacteria in 5–10 μ m diameter capillaries pose several challenges. The Immersed Boundary Method (IBM) was used to resolve the capillary, deformed RBCs, and bacteria. The challenge of disparate coupled time scales of flow and bacteria motion are reconciled by a temporal multiscale simulation method. Bacterium-wall and bacterium-RBC collisions were detected using a hierarchical contact- detection algorithm. Motile bacteria showed a net outward radial velocity of 2.8 µm/s compared to −0.5 µm/s inward for non-motile bacteria; thus, exhibiting a greater propensity to escape the bolus flow region between RBCs and marginate for potential extravasation, suggesting motility enhances extravasation of bacteria from capillaries.